An examination of contemporary works for wind band: Jubilance by James Swearingen, Music For A Celebration by Dirk Brossé, and Variations On A Ninth by James Curnow - Thomas, Preston Wayne (Kansas State University, 2023)
This thesis analyzes three concert band pieces: Jubilance by James Swearingen, Music For A Celebration by Dirk Brossé, and Variations On A Ninth by James Curnow. Each analysis details the composer, a general overview of the composition, the historical relevance, the technical considerations, the stylistic considerations, musical considerations (melody, harmony, rhythm, and timbre), the form, and other similar pieces. This thesis aims to allow directors who are potentially selecting this piece, or who have selected this piece, for their concert band ensemble to perform to have a guide that details what makes the piece unique and what concepts the piece can teach. Also included in this thesis is the authors' philosophy of why music education is vital to all people and why it is essential to choose literature that improves ensemble musicianship.
Keywords: James Swearingen; Dirk Brossé; James Curnow; Analysis; Concert band; Music